Broader impacts of an intervention to transform school environments on student behaviour and school functioning: post hoc analyses from the INCLUSIVE cluster randomised controlled trial - Bonell, C; Dodd, M; Allen, E; Bevilacqua, L; McGowan, J; Opondo, C; Sturgess, J; Elbourne, D; Warren, E; Viner, RM (BMJ Publishing Group, 2020)
Background We have previously reported benefits for reduced bullying, smoking, alcohol and other drug use and mental health from a trial of ‘Learning Together’, an intervention that aimed to modify school environments and implement restorative practice and a social and emotional skill curriculum.